Response to comment on "A high-precision 40Ar/39Ar age for the Nördlinger Ries impact crater, Germany, and implications for the accurate dating of terrestrial impact events" by Schmieder et al. (Geochimica et Cosmochimica Acta 220 (2018) 146–157). (1st October 2018) - Schmieder, Martin; Kennedy, Trudi; Jourdan, Fred; Buchner, Elmar; Reimold, Wolf Uwe
Abstract: Rocholl et al. (2018) claim that the 40 Ar/ 39 Ar age of 14.808 ± [0.038] Ma (2σ; full external error) for the Ries impact, recently obtained from step-heating analysis of tektites (Schmieder et al., 2018, Geochim. Cosmochim Acta 220, 146–157), is " geologically impossible " and violates paleomagnetic constraints. We demonstrate that the moldavite age of Schmieder et al. (2018) is in good agreement with recalculated isotopic ages for ash layers and magnetic (sub-)chrons that define the Langhian stage in the Astronomically Tuned Neogene Time Scale, using updated K decay constants and monitor ages in 40 Ar/ 39 Ar geochronology. Moreover, we stress that the normally magnetized basal pelitic sediments of the Ries crater lake, which are separated from the reversely magnetized suevite by a thick unit of post-impact conglomerates and sandstones, may not have been deposited 'immediately' after the impact. The paleomagnetic constraints proposed by Pohl (1977, 1978) and Rocholl et al. (2018) are, therefore, questionable.